A arte nova e o novo na arte na filosofia de Theodor W. Adorno - Luciana Molina Queiroz (2014)
This dissertation aims at providing an interpretation of the philosophy of Theodor W. Adorno that problematizes the status of the new art. The importance of this issue is due to the understanding, supported by Adorno, that the search for the new in modern art is also implicit in commodity fetishism. The proposal is to differentiate the appearance of novelty of the culture industry and new in art, emphasizing how the latter ensures authenticity of art. In order to fulfill this goal, we intend to show that the new in modern art, more than a modernist ideology, derives from how Adorno interprets the dialectical tradition and the romantic conception of originality. The philosopher appreciates the nominalist artwork that does not meet the generic concept of art. In criticizing the conventions of artistic tradition, new art rejects the generic concept of art. At the same time, it constitutes a determinate negation of society. Thus, it is possible to understand Entkunstung, the loss of specificity of art, as a critical strategy in relation to art and society. Adorno refuses eschatological discourses on art (common in Hegelian-Marxist classical tradition) that declare the death or decay of art. Instead of accepting the pessimist diagnosis about modern art, Adorno recognizes the critical character of new art.